Optimization and Coordination of HAFDV PINN Control by Improved PSO - Bin Huang; Nengling Tai; Wentao Huang (Journal of Control Science and Engineering)
The new hybrid active filter (HAF) is composed of the larger-capacity passive filter banks and the smaller-capacity active filter. It is difficult to tune the parameters of a PI controller using the DC capacitor voltage control. In this paper, the improved particle swarm optimization (improved PSO) algorithm is proposed to solve the coordinated design problem, and the neural network weights as the particle swarm optimization are adopted to optimize the system parameters. Comparing with the conventional PI controller, the results of PINN controller prove the effectiveness of designed method on both the transient and steady-state performance of the hybrid active filter DC bus voltage (HAFDV) controllers.